(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2023)
Materials and methods: herbarium collections, literature data, field observations. Nomenclature: POWO 2023. Results: The order Saxifragales (incl. Crassulales, Grossulariales, Haloragales) is represented in the flora of Ukraine by taxa of four families: Crassulaceae, Grossulariaceae, Haloragaceae, and Saxifragaceae. The most species-rich (considering both native and introduced species) families of the order in Ukraine are Crassulaceae (47 species) and Saxifragaceae (24). The family Crassulaceae is represented by 10 genera: Crassula (incl. Tillaea – 2 species), Echeveria (1), Graptopetalum (1), Hylotelephium (8), Kalanchoë (1), Petrosedum (3), Phedimus (5), Rhodiola (1), Sedum (incl. Macrosepalum – 18), and Sempervivum (incl. Jovibarba – 7 species). There are 6 genera in Ukraine belonding to the family Saxifragaceae: Astilbe (1), Bergenia (1), Chrysosplenium (2), Heuchera (1), Micranthes (2), and Saxifraga (17). Grossulariaceae and Haloragaceae are represented by one genus each: Ribes (incl. Grossularia) – 9 species, and Myriophyllum (3), respectively. The order Solanales includes the families Convolvulaceae (incl. Cuscutaceae) and Solanaceae. The family Convolvulaceae (including Cuscutaceae) is represented by four genera (Calystegia, Convolvulus, Cuscuta, Ipomoea) with 32 species and intraspecific taxa, many of which are weeds, parasitic, and, partly, ornamental plants. The family Solanaceae is represented by 14 genera and 32 species, some of which are cultivated. As compared to the previous version of the checklist (Mosyakin & Fedoronchuk 1999), there were significant changes in the species composition and their nomenclature in the genera Calystegia, Convolvulus, Cuscuta, Physalis, and Solanum. Some taxa underwent changes in their taxonomic rank (e.g., were reduced to subspecies or varieties) or were transferred to synonymy; some are new or previously not listed in relevant earlier publications (e.g., Convolvulus calvertii subsp. ruprechtii, Cuscuta planiflora, Ipomoea batatas, Solanum retroflexum). The genus Physalis sensu lato underwent taxonomic and nomenclatural changes and, on the basis of recent molecular phylogenetic studies and subsequent nomenclatural conservaeion, was split into Physalis s. str. and he monotypic genus Alkekengi, with the conserved nomenclatural type Alkekengi officinarum (≡ Physalis alkekengi).